Semiautomatic Extraction of Road Horizontal Alignment from a Mobile LiDAR System. (10th September 2014) - Holgado‐Barco, Alberto; González‐Aguilera, Diego; Arias‐Sanchez, Pedro; Martinez‐Sanchez, Joaquin
Abstract This article proposes a method to semiautomatically extract the road axis through a mobile LiDAR system, a recent popular technology for transportation‐related applications, road estimation and even to enhance driver safety. In particular, the approach developed has two components: (1) the feature extraction from LiDAR data to model the road axis, and (2) the estimation of the horizontal alignment that meets the requirements and practice for a transportation authority. Given the massive and complex character of the data captured by the system, a hierarchical (coarse‐to‐fine) and robust strategy based on segmentation, parameterization and filtering, which determine the road centerline together with the geometric elements that compose its horizontal alignment, such as straight lines, circular arcs, and clothoids, has been developed and implemented. Test results using a simulated and a real data are discussed and validated. The experimental results obtained with real cases guarantying relative accuracies under 2%, being a useful approach to produce accurate estimations of the horizontal geometric features of the road alignment.